IMPLEMENTASI METODE DEMONSTRASI DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PADA MASA PANDEMI COVID-19 DI SLB MELATI RUMBAI - Maidar Maidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Based on the observations, there are irregularities in the teacher's ability to teach. This can be seen from the symptoms, among others, There are still teachers who are not able to develop a learning syllabus, they only use the old syllabus, There are still those who have not been able to manage the class properly and properly, There are still teachers who have not been able to interact and communicate well with students., There are still teachers who have not been able to allocate time properly. There are still teachers who do not motivate students to be actively involved in the learning process. This study aims to determine whether the teacher's pedagogical competence can be improved by using the demonstration method at SLB Melati Rumbai Pekanbaru City. Based on the background description, problem identification and problem limitation, the focus of this research relates to the Implementation of the Demonstration Method in Improving Teacher Pedagogic Competence during the Covid-19 Pandemic at SLB Melati Rumbai Pekanbaru City. This School Action Research was carried out only at SLB Melati Rumbai Pekanbaru City. This research was conducted in two cycles. The duration of this research is approximately 1 month. From the description of data processing and discussion, it was concluded that the teacher's pedagogic competence was obtained in the first cycle of 65% in the good category and in the second cycle increased to 87% in the very good category.